2017
DOI: 10.1101/193078
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Defective synapse maturation and enhanced synaptic plasticity in Shank2-/-mice

Abstract: SummaryAutism spectrum disorders (ASDs) are neurodevelopmental disorders with a strong genetic aetiology. Since mutations in human SHANK genes have been found in patients with autism, genetic mouse models are employed for a mechanistic understanding of ASDs and the development of therapeutic strategies. In sharp contrast to all studies so far on the function of SHANK proteins, we observe enhanced synaptic plasticity in Shank2-/-mice, under various conditions in vitro and in vivo. Reproducing and extending prev… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 36 publications
(29 reference statements)
1
5
0
Order By: Relevance
“…Although some data suggest that LTP changes match with analogous modifications of memory processes, many studies investigating different genetically modified mouse strains report clear dissociation of LTP and memory, challenging the causal relationship between these two processes. [58][59][60] Consistent with these studies, in macroH2A1.1 −/− mice an increased hippocampal E-LTP is not associated with enhanced cognitive performance. This apparent discrepancy at least could be sought in the complexity of the processes and multitude of cerebral areas interacting each other in information storage.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Although some data suggest that LTP changes match with analogous modifications of memory processes, many studies investigating different genetically modified mouse strains report clear dissociation of LTP and memory, challenging the causal relationship between these two processes. [58][59][60] Consistent with these studies, in macroH2A1.1 −/− mice an increased hippocampal E-LTP is not associated with enhanced cognitive performance. This apparent discrepancy at least could be sought in the complexity of the processes and multitude of cerebral areas interacting each other in information storage.…”
Section: Discussionsupporting
confidence: 75%
“…MacroH2A1.1 did not appear to be involved in hippocampus‐dependent forms of memory, but we observed changes in E‐LTP. Although some data suggest that LTP changes match with analogous modifications of memory processes, many studies investigating different genetically modified mouse strains report clear dissociation of LTP and memory, challenging the causal relationship between these two processes 58–60 . Consistent with these studies, in macroH2A1.1 −/− mice an increased hippocampal E‐LTP is not associated with enhanced cognitive performance.…”
Section: Discussionmentioning
confidence: 83%
“…Our study revealed a novel zinc/Shank-dependent molecular pathway for regulating AMPAR subunit switching that could affect the formation, maturation and plasticity of excitatory synapses. Consistently, alterations of AMPAR subunit compositions and/or synaptic recruitment have been seen in multiple Shank2 and Shank3 mouse KO models of ASDs (Ramanathan et al, 2004 ; Mejias et al, 2011 ; Hayashi et al, 2013 ; Mignogna et al, 2015 ; Bariselli et al, 2016 ; Chanda et al, 2016 ; Wegener et al, 2017 ). Our findings also offer a novel mechanism for understanding how zinc deficiency or disrupted zinc dynamics might be linked to individuals with ASDs (Yasuda et al, 2011 ; Grabrucker et al, 2014 ; Curtin et al, 2018 ).…”
Section: Discussionmentioning
confidence: 72%
“…Shank2 and Shank3 have also been implicated in the maturation of synapses. For example, loss of Shank2 in mice resulted in reduced GluA1 levels, delayed synaptic maturation, and a reduction of AMPA receptor (AMPAR) function (Peter et al, 2016 ; Wegener et al, 2017 ). Similarly, Shank3 was shown to play a key role in the postnatal development of excitatory synapses, such that loss of Shank3 increased the AMPA/NMDA ratio and impaired the developmental AMPAR subunit switch (Peça et al, 2011 ; Bariselli et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Mutations in human Shank genes are also found in ASD (Durand et al, 2007 ; Berkel et al, 2010 ; Sato et al, 2012 ) and expected to relate to their role in activity-dependent formation and remodeling of synaptic function. Analysis in a mouse model of Shank2, lacking exons 6 and 7, showed reduced hippocampal NMDAR function, whereas mice lacking only exon 7 show up-regulation of NMDARs in synaptosomes, increased NMDAR/AMPAR ratio, and enhanced NMDAR dependent LTP (Wegener et al, 2018 ). We can model this condition by varying the equilibrium constant value of k or kNMDAR.…”
Section: Introductionmentioning
confidence: 99%